2005
DOI: 10.1529/biophysj.104.057745
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of DM-Nitrophen Binding to Calcium and Magnesium

Abstract: Caged-Ca(2+) compounds such as nitrophenyl-EGTA (NP-EGTA) and DM-nitrophen (DMn) are extremely useful in biological research, but their use in live cells is hampered by cytoplasmic [Mg(2+)]. We determined the properties of Ca(2+) release from NP-EGTA and DMn by using Oregon green BAPTA-5N to measure changes in [Ca(2+)] after ultraviolet flash photolysis in vitro, with or without Mg(2+) present. A large fraction (65%) of NP-EGTA, which has a negligible Mg(2+) affinity, uncages with a time constant of 10.3 ms, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 21 publications
6
44
1
Order By: Relevance
“…In the axon, the fluorescence change, ΔF/F 0 , due to Ca 2+ release by laser pulse photolysis (Fig. 2) showed a sharp rise in <1 ms, consistent with rapid Ca 2+ release by photolysis of DM-nitrophen-Ca 2+ , which has been reported to have a 15-μs time constant (26). The mean decay time constant of Ca 2+ -induced fluorescence was 120.7 ± 63.5 ms (mean ± SD; n = 49 regions of interest from 18 different cells; single laser pulses 0.1-1 ms in duration, energies 0.2-5 μJ at the cell).…”
Section: Resultssupporting
confidence: 67%
“…In the axon, the fluorescence change, ΔF/F 0 , due to Ca 2+ release by laser pulse photolysis (Fig. 2) showed a sharp rise in <1 ms, consistent with rapid Ca 2+ release by photolysis of DM-nitrophen-Ca 2+ , which has been reported to have a 15-μs time constant (26). The mean decay time constant of Ca 2+ -induced fluorescence was 120.7 ± 63.5 ms (mean ± SD; n = 49 regions of interest from 18 different cells; single laser pulses 0.1-1 ms in duration, energies 0.2-5 μJ at the cell).…”
Section: Resultssupporting
confidence: 67%
“…The most detailed in vitro study on the binding parameters of CR was carried out by applying the same methodology, i.e., release of caged Ca 2+ from DM-nitrophen [174], as used before for the determination of the binding properties of CB-D28k [125]. The prior determination of the kinetic properties of DM-nitrophen, i.e., its binding to Ca 2+ and Mg 2+ [175] was a requirement for the accurate modeling of CR. Faas and co-workers [174] developed a new mathematical model to determine the dynamic properties of cooperative binding to gain a better understanding of the physiological implications of cooperativity.…”
Section: B Schwaller Ca2+ Buffersmentioning
confidence: 99%
“…We combined the voltage-clamp fluorometry technique (40 -42) with the UV photolysis of a Ca 2ϩ cage compound, DM-Nitrophen (43)(44)(45)(46), to simultaneously trigger voltage-and Ca 2ϩ -dependent activations of BK channels. We found that rapid intracellular Ca 2ϩ release produced structural rearrangements that not only increased channel P o but also perturbed the conformation of the S4 helix of the BK VSD.…”
mentioning
confidence: 99%